2008
DOI: 10.1667/rr1231.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hematological Malignancies among Chernobyl Liquidators

Abstract: A case-control study of hematological malignancies was conducted among Chernobyl liquidators (accident recovery workers) from Belarus, Russia and Baltic countries in order to assess the effect of low-to-medium dose protracted radiation exposures on the relative risk of these diseases. The study was nested within cohorts of liquidators who had worked in 1986–87 around the Chernobyl plant. 117 cases (69 leukemia, 34 non-Hodgkin Lymphoma (NHL) and 14 other malignancies of lymphoid and hematopoietic tissue) and 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 22 publications
5
80
1
2
Order By: Relevance
“…8 Increased risks of leukemia, although not statistically significant, were reported from a study of Chernobyl cleanup workers from Belarus, Russia, and Baltic countries. 9 Similar findings were reported for Russian cleanup workers from the analysis based on the official reported doses and the Chernobyl Registry-based leukemia diagnoses. 10 We recently reported the results of 20-year follow-up of a cohort of 110,000 cleanup workers from Ukraine.…”
Section: Leukemia In Chernobyl Cleanup Workerssupporting
confidence: 76%
“…8 Increased risks of leukemia, although not statistically significant, were reported from a study of Chernobyl cleanup workers from Belarus, Russia, and Baltic countries. 9 Similar findings were reported for Russian cleanup workers from the analysis based on the official reported doses and the Chernobyl Registry-based leukemia diagnoses. 10 We recently reported the results of 20-year follow-up of a cohort of 110,000 cleanup workers from Ukraine.…”
Section: Leukemia In Chernobyl Cleanup Workerssupporting
confidence: 76%
“…In addition, Cardis et al (23) showed that there was a significant increase in the risk of certain cancers in workers of nuclear facilities (24). Radiation in the form of radioiodine is also used as a treatment for thyroid cancer albeit at higher doses (25), although studies have explored the possibility of using lower doses of radiation in cancer therapy for certain cancers (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no increase in the median number of foci per nucleus at the lowest irradiation dose compared to the control: 0 (0-0) vs. 0 (0-0) foci/nucleus [median (interquartile range)]. Only at the higher doses was there an increase to 2 (0-9) for 0.5 Gy, and 26 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) foci per nucleus for 4 Gy ( Fig. 2A), both significant at p<0.05.…”
Section: Irradiation Causes An Increase In Amount Of Dsbs In Tpc-1 Cementioning
confidence: 94%
“…Prisyazhniuk et al stated statistically significant increment in observed-to-predicted ratio of leukemia and lymphoma incidence: 2.6 in 1990-1993 and 2.0 in 1994-1997 [8] . Kesmeniene et al reported on 117 cases of neoplasms of lymphoid and hematopoietic tissues in Belarus, Russia and Baltic countries as of 2007 [9] . In a study of the cohort of male clean-up workers in Ukraine subjected to the external radiation exposure, the investigators at the National Cancer Institute (USA) observed a radiation-related risk of leukemia comparable to risks experienced by Japanese atomic bomb survivors with acute exposure [10] .…”
Section: Introductionmentioning
confidence: 99%